Applying Lean Healthcare in the hospitalization and patient discharge process: an integrative review - Livia Barrionuevo El Hetti Fuentes; Lucas Gardim; Thaís Oliveira da Silva; André Almeida de Moura; Andrea Bernardes (Revista Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to identify scientific evidence regarding the use of Lean Healthcare approach in the hospitalization and patient discharge process. Methods: this is an Integrative Review conducted in the PubMed, LILACS, SCOPUS, CINAHL, Web of Science, and Embase databases. Results: out of 904 records identified, three were included in this review. The studies demonstrated that when applied to discharge planning, the Lean philosophy brings favorable results, promoting improvements in the communication process, as well as assisting in workflow organization, with a reduction in length of stay and improvement in the quality of care. Final Considerations: although the Lean methodology presents positive results, it is considered that the application of the philosophy in healthcare institutions is still not sustainable, as it is often restricted to specific departments or services. Thus, to maximize the success of implementation, the Lean philosophy needs to be incorporated into the organizational culture, representing the greatest challenge.